Potential for Utilizing POME to Produce Biohydrogen Gas Using Microbial Electrolysis Cell - Ferdy Christian Hartanto; Nadia Nurul Atikah; Mohammad Sahid Indrawan; Armansyah Halomoan Tambunan (International Journal of Oil Palm, 2022)
Palm oil mill effluent contains organic matter and microorganisms that can potentially be reused despite of its impact to the environment. Microbial electrolysis cell is a method that utilizes electrogenic bacteria to produce hydrogen gas. This study aims to explore the potential for utilizing palm oil mill effluent to produce hydrogen gas using microbial electrolysis cells. Experiments were conducted in a specially built MEC reactor with a 3.5 L capacity with 0.5, 1.0, and 1.5 V with carbon fiber cloth as electrodes. A gas analyzer was used to measure hydrogen gas over the course of 24 h at a 2 h interval. Palm oil mill effluent was utilized as a substrate, while distilled water was used as a control. Experiments demonstrate that the amount of hydrogen gas produced increases as the voltage increases, with values of 37 mg m-3 at 0.5 V, 136 mg m-3 at 1.0 V, and 358 mg m-3 at 1.5 V. When comparing the yield of hydrogen gas produced with distilled water substrate at 1.5 V, the yield of palm oil mill effluent substrate is always higher. This could be due to microbial activity increasing the rate of electrolysis of the substrate into hydrogen gas.